1047 A Community-Based Sleep Health and Yoga Intervention to Improve Sleep Outcomes among Low-income and Racial/Ethnic Minority Adults. (27th April 2018) - Spadola, C; Zhou, E S; Rottapel, R; Gou, N; Johnson, D A; Weng, J; Chen, J; Redline, S; Bertisch, S M
Abstract: Introduction: Inadequate sleep is highly prevalent among socioeconomically disadvantaged and racial/ethnic minority communities, and is often related to sleep health behaviors, stress, and adverse environmental conditions. While socio-contextually appropriate sleep health education and yoga interventions may improve sleep and mitigate adverse effects and reactivity to environmental stressors, there is scant research specifically addressing how to effectively deliver these interventions in underrepresented communities. Methods: We conducted a pilot study of a combined sleep health and yoga intervention among racially/ethnically diverse adults residing in low-income housing communities, who reported sleeping less than 6 hours a night (n=23). The intervention consisted sequentially of: one group sleep health education session (1-hour), one telephone coaching session (15 minutes), and four weekly 1-hour yoga classes. Two-tailed Wilcoxon Signed-Rank tests assessed pre- and post-intervention changes in self-reported sleep duration, scores from the PROMIS Sleep-Related Impairment and Sleep Disturbance Short Forms, Sleep Hygiene Index, and validated stress and mood assessments. Quantitative and qualitative data assessed intervention acceptability. Results: Mean participant age was 41.4 years ± 19.6; 80.7% were female; 61.5% identified as non-Hispanic Black and less than 20% had a college degree. Results showed significant pre/post intervention improvements in sleep duration (5.3 ± 0.9 hours/night versus 7.2 ± 1.7 hours/night [p=.02]), sleep-related impairment (p=.002), sleep disturbance (p=.002), and sleep health behaviors (p=.021). Attendance (100% received sleep health education; 47.8% attended at least 2 of 4 yoga classes), intervention feedback scores (73.7% rated the sleep education session as helpful or very helpful; 63.2% strongly agreed that the yoga class left them feeling relaxed and less stressed), and qualitative data (e.g., "What I liked least about the program was when it ended, because it was so good") support the acceptability of the intervention. Conclusion: Pilot study results indicate intervention acceptability and promising effects on improvement of sleep disturbance, sleep-related impairment, and sleep health behaviors. A larger, randomized control trial is planned to elucidate and disentangle the effects of sleep health education and yoga practice on sleep. Support (If Any): NIH #R34AT008923.